Tax Culture of Employees of the Enterprise - V. P. Panteleiev; M. V. Nastenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
By the standard of relation of workers of enterprise to implementation of duties in relation to tax payment in a budget there must be an imperative of the USA and most capitalist countries: taxes are paid undoubtedly in the rules and terms marked Law. In these countries cultural traditions and honor are formed and supported to supremacy of interests of society and state. 'Tax culture of workers' as interdisciplinary study, proposing his phenomenon that was not able to have a presentiment in any other way. With hope, we will testify the theory of tax culture, that confidently moves after clean hypothetical political, economic, and social study, in the near future. Besides, reasoning recommendations can be got from the concept of tax culture of workers, that in the end will result in higher and more viable tax profits to more legal tax state as well as more transparent tax mode.The article reveals measures to introduce tax culture, which contribute to the motivational mechanism of economic regulation. The role of the tax culture in the field of taxation is described, the rules for the implementation of tax culture at the enterprise of Ukraine in the administration of taxes and fees are set forth, the author's definition of tax culture is formulated, the experience of EU countries in using cultural traditions in accounting for tax liabilities and the application of effective management tools is shown; the sequence of promotion of the problems of tax administration with application of tax culture is given.